The 5Q approach for gender data on empowerment in climate adaptation projects: Case study in Ghana - Eitzinger, Anton; Nikoi, Gordon; Slavchevska, Vanya; Bonilla-Findji, Osana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Our research validates the 5Q approach (5Q) for the collection of gender data on empowerment in climate adaptation projects. 5Q was developed as a cost-effective and innovative system for capturing near-real-time feedback within projects. 5Q uses smart-question-trees (5Q-SQTs) and digital tools to complement traditional methods of data collection. It has been widely used to measure changes in knowledge/attitudes/skills to understand the adoption of climate-smart agricultural (CSA) practices and for M&E systems of climate-smart villages. It uses simple sets of questions part of a logic-question-tree structure, implemented at multiple rounds, thus simplifying the burden for respondents while rapidly and with high frequency providing feedback to the project implementers.